Bihar Second Five-Year Plan Progress Report for the Period Ending March 1958 - Planning Commission (Planning Commission, 1958)
Agriculture and Community Development, Agricultural Production, Minor Irrigation, Soil Conservation, Land Development, Marketing, Animal Husbandry, Dairying and Milk Supply, Forest, Fisheries, C.P. and N. E. S., Co-operation, Irrigation and Power
Bihar